A Research Article On Agnikarama In Vatakantaka With Special ReferenceTo Plantar Fasciitis - Hiteshi (International Research Journal of Ayurveda & Yoga, 2021)
Plantar Fasciitis is a painful condition in which there is an inflammation of a thick band of tissue that runs across the bottom of foot. Plantar fascia is a broad, thick band of tissue, that run from under the heel to the front of foot. Plantar fasciitis commonly causes stabbing pain and is one of the cause of heel pain. Plantar fasciitis is also known as Heel spur which is common in runners, dancers and is seen in patients of middle age group i.e 35-60 yrs old. Acharya Sushruta suggests that the disease Plantar fasciitis can be correlated with Vatakantaka in Ayurveda. Vatakantaka is a condition resulting due to Kapha-vata vitiation and is caused by walking on uneven surfaces or by Ati shrama, which produces Ruja in Khadula Pradesha (Paarshani Padajangha Sandhi). It is a Vata Pradhana Vyadhi and Acharya Sushruta hails Agnikarma procedure as the best and most important procedure. While elaborating the benefits of this procedure, he mentions that the procedure is easy to perform. It cures many incurable diseases and there will be no recurrence of the disease. In the present study,30 patients of Vatakantaka were selected. Study was carried out for 2 weeks, 1 sitting per week.